Towards assessing the impact of tourism on health in developing countries : exploring Peruvian villagers' concepts of prerequisites for good community health - Bauer, Irmgard (Curtin University, 2010)
Background: Tourism is one of the largest global industries, forecasting 1.6 billion international arrivals by 2020. This growth includes destinations in the developing world. This is also there where negative economic, environmental and social impacts of developments, including tourism, are particularly pronounced and have attracted much attention in the literature. To date, there has been little focus on the implications of tourism for the health status of rural and remote destination communities. Globally, impact assessments are now an integral part of project applications, but no tool exists to measure tourism's health impacts. Furthermore, the power imbalance between the 'expert' assessors who choose measurement criteria and conditions and the affected people who have to live with the impact has long been criticised. Therefore, the aim of this study was to prepare the ground for the development of community-validated indicators for an assessment tool that can be used by target communities to make decisions for or against the acceptance of a tourism project.Methods: First, to inform the design of a Tourism Health Impact Assessment Tool (TOHIAT), 35 people from two remote villages in the Peruvian Cordillera Huayhuash cooperated in identifying prerequisites for a healthy community. Unstructured interviews and a rank-order method were employed to describe people's views on core concepts and their relative importance for community-well-being. Second, an additional extensive critical analysis of the literature after the fieldwork examined the position of poor destination communities in developing countries from health, tourism, development, and poverty perspectives. This allowed a reflection on issues that had emerged during the fieldwork, such as the notions of community, power and outsider intervention.Findings: Six concepts (work, individual health, education, family, environment and harmony) emerged to represent the basis for the indicator development of the TOHIAT which can be utilised by various stakeholders, but primarily by the affected communities themselves. The findings from the fieldwork and the reflection of the literature provided 1) information as a basis for the development of an impact assessment tool customised for the study locations and 2) a description of how every attempt was made to ensure that local people's needs, views and decisions were afforded priority. Additional and alternative research methods to elicit local people's voices are suggested for replication here and in similar settings around the world.Conclusions: This study represents the first step in the process of the TOHIAT design and implementation. More importantly, it makes an invaluable contribution to redress the issues of power inequality, marginalisation and exploitation of poor people in the name of profit for the global tourism industry.